Electron beam irradiation of combined pharmaceuticals: propranonol and fluoxetine and related ecotoxicity (Brazilian Journal of Radiation Sciences (BJRS), 2021)
There are serious evidences that justify the search for treatment technologies or processes combination for the improvement of decomposition for dozens of pharmaceuticals in wastewaters. Electron beam irradiation may play an important role in this scenario and relatively low doses have been reported for such purposes. The aim of the present study was to evaluate the toxic response of the crustacean Daphnia similis exposed to individual and combined pharmaceuticals, before and after electron beam irradiation treatment. Several experimental trials of an acute immobilization test were performed with a mixture of pharmaceuticals composed of fluoxetine hydrochloride (Prozac®), and propranolol. Single pharmaceuticals were first tested separately. Toxicity of binary mixture was then assessed using five concentrations and five percentages of each substance in the mixture (0, 25, 50, 75, and 100%). Acute EC50% values ranged from 5.0 to 7.4 for fluoxetine and from 11.3 to 13.7 for propranolol. In mixture, values ranged from 6.4 to 9.8. Fluoxetine was more toxic than propranolol for D.similis. The different pharmaceuticals concentrations employed in a mixture showed no difference in toxicity values. When electron beam irradiation was applied, approximately 80% of acute effects were reduced at 5 kGy, and the mixture containing a higher percentage of fluoxetine, also showed a greater reduction of toxicity.